Stabilizing an amyloidogenic λ6 light chain variable domain. (12th October 2017) - Luna‐Martínez, Oscar D.; Hernández‐Santoyo, Alejandra; Villalba‐Velázquez, Myriam I.; Sánchez‐Alcalá, Rosalba; Fernández‐Velasco, Daniel A.; Becerril, Baltazar
Abstract : Light chain amyloidosis is a lethal disease where vital organs are damaged by the fibrillar aggregation of monoclonal light chains. λ6a is an immunoglobulin light chain encoded by the germ‐line gene segment implicated in this disease. AR is a patient‐derived germ‐line variant with a markedly low thermodynamic stability and prone to form fibrils in vitro in less than an hour. Here, we sought to stabilize this domain by mutating some residues back to the germ‐line sequence, and the most stabilizing mutations were the single‐mutant AR‐F21I and the double‐mutant AR‐F21/IV104L, both located in the hydrophobic core. While mutation Arg25Gly in 6aJL2 destabilized the domain, mutating Gly25 back to arginine in AR did not contribute to stabilization as expected. Crystallographic structures of AR and 6a‐R25G were generated to explain this discrepancy. Finally, 6a‐R25G crystals revealed an octameric assembly which was emulated into 6aJL2 and AR crystals by replicating their structural parameters and suggesting a common assembly pattern. Database: The atomic coordinates and structure factors have been deposited in the Protein Data Bank under the accession numbers5IR3 and5C9K . Abstract : In this work, an octameric assembly of a mutant variable domain is described. This might represent an important early stage in amyloid aggregation since this feature is apparently shared between its immunoglobulin germ line and a patient‐derived light chain analyzed here as well.